Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1365-2958.1997.5701931.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of architectural elements in combinatorial regulation of initiation of DNA replication in Escherichia coli

Abstract: SummaryBending of DNA is a prerequisite of site-specific recombination and gene expression in many regulatory systems involving the assembly of specific nucleoprotein complexes. We have investigated how the uniquely clustered Dam methylase sites, GATCs, in the origin of Escherichia coli replication (oriC ) and their methylation status modulate the geometry of oriC and its interaction with architectural proteins, such as integration host factor (IHF), factor for inversion stimulation (Fis) and DnaA initiator pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Adenine methylation can alter the interactions of regulatory proteins with DNA, either by a direct steric effect or by an indirect effect on DNA structure (18,61,62). Initial studies with dam mutants showed that Dam regulates the expression of certain genes in E. coli including trpR (60), Tn10 transposase (68), and dnaA (13) as well as phage genes including mom of Mu (24).…”
Section: Dam Familymentioning
confidence: 99%
“…Adenine methylation can alter the interactions of regulatory proteins with DNA, either by a direct steric effect or by an indirect effect on DNA structure (18,61,62). Initial studies with dam mutants showed that Dam regulates the expression of certain genes in E. coli including trpR (60), Tn10 transposase (68), and dnaA (13) as well as phage genes including mom of Mu (24).…”
Section: Dam Familymentioning
confidence: 99%
“…A DNA methylation pattern is formed by binding of a regulatory protein(s) to a site that overlaps a methylation target, blocking methylation. This pattern can control gene expression if methylation, in turn, affects binding of the regulatory protein(s) to its DNA target site, which could occur by steric hindrance or alteration of DNA structure due to methylation (206,207). Notably, most adhesin genes in E. coli are regulated by epigenetic mechanisms involving DNA methylation patterns (32,115,116,262).…”
Section: Introductionmentioning
confidence: 99%
“…IHF is a multipurpose architectural protein, which plays an essential role in several cellular processes including sitespecific recombination, transcription, DNA replication, and phage packaging (16)(17)(18)(19). The crystal structure of IHF bound to the HЈ site indicates that the DNA is kinked at two sites separated by Ϸ9 bp and that the overall bend in the DNA is Ϸ160° (Fig.…”
mentioning
confidence: 99%